Numerical simulation of oil spills based on the GNOME and ADIOS - Elizaryev, A; Maniakova, G; Longobardi, A; Elizareva, E; Gabdulkhakov, R; Nurutdinov, A; Khakimov, R (International Journal of Engineering and Technology, 2018)
The Exxon Valdez oil spill emergency has shown that simulation of oil spills trajectory is the main action in planning response measures. Modeling the trajectory of the oil slick allows predicting in advance the direction of the motion of the stain, the time it will take to reach the shore and assess the possible environmental consequences for the contaminated coastal zone. In this paper, the Exxon Valdez oil spill trajectory was analyzed using two different models, the GNOME model and the HAZAT trajectory model. Conclusions are drawn about the reasons for the differences in the results provided by the two models. The accuracy of the simulation is strongly related to the input of geographic and meteorological data. In addition, ADIOS software was used to predict the weathering process of the modeled emergency event. It was found that the main factors influencing the change in the physical and chemical characteristics of oil dispersed in the water body are the wind speed and direction, water temperature and wave height.Â Â